Does Obesity Affect Neuromuscular and Cardiovascular Adaptations after a 3-Month Combined Exercise Program in Untrained Premenopausal Middle-Aged Women? - Konstantina Karatrantou; Vassilis Gerodimos (MDPI AG, 2023)
Previous studies indicated different acute adaptations between obese and lean individuals, while there is limited information with conflicting results regarding long-term adaptations. The aim of this study was to compare the efficacy of a 3-month integrated combined training between obese and lean middle-aged untrained premenopausal women. In total, 72 women (36 obese/36 lean) were divided into four groups: (a) obese exercise (OB-EG), (b) obese control (OB-CG), (c) lean exercise (L-EG), and (d) lean control (L-CG). The exercise groups followed a 3-month (3 times/week) integrated combined aerobic and strength training program. Health indices (body composition, body circumferences, blood pressure, respiratory function), functional capacity (flexibility, balance), and physical fitness (strength, aerobic capacity) were measured before and after the 3-month time period. Participants' enjoyment was also assessed following the program. OB-EG and L-EG significantly improved (p < 0.05) similarly across all functional capacity and physical fitness indices (10-76%; depending on the evaluation index), except balance and strength indices of the non-preferred limb where OB-EG showed greater improvement (reducing the existing pre-training strength/balance asymmetries) than L-EG. Furthermore, both obese and lean individuals showed similarly high levels of enjoyment. This program could be effectively used in fitness settings causing similar neuromuscular and cardiovascular adaptations in obese and lean women.